Tunable wideband absorber based on resistively loaded lossy high-impedance surface - 党可征 时家明 汪家春 林志丹 王启超 (Chinese physics B, 2015)
A lossy high-impedance surface comprised of two layers of resistive frequency selective surfaces is employed to design a tunable electromagnetic absorber. The tunability is realized through changing the composite unit cell by moving the top layer mechanically. To explain the absorbing mechanism, an equivalent circuit model with an interacting coefficient is proposed. Then, simulations and measurements are carried out and agree well with each other. Results show that the complex structure with a thickness less than λ0/4 is able to achieve a wideband absorption in a frequency range from5.90 GHz to 19.73 GHz. Moreover, it is tunable in the operation frequency band.